2015
DOI: 10.3389/fmats.2015.00038
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated and Saturated Permeabilities of Fiber Reinforcement: Critics and Suggestions

Abstract: In general, permeability measurement results show a strong scattering according to the measurement method, the type of test fluid and the fluid injection condition, even though permeability is regarded as a unique property of porous medium. In particular, the discrepancy between the unsaturated and saturated permeabilities for the same fabric has been widely reported. In the literature, relative permeability has been adopted to model the unsaturated flow. This approach has some limits in the modeling of double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…However, it has been reported that the saturated and unsaturated permeability values can differ for the same reinforcement [23][24][25][26][27]. In many cases, the saturated permeability values exceed the unsaturated permeability values [23][24][25][26][27][28]. Many possible reasons for this discrepancy have been reported; capillary effects, void entrapment, and fiber deformation problems, etc.…”
Section: Background and Theorymentioning
confidence: 99%
“…However, it has been reported that the saturated and unsaturated permeability values can differ for the same reinforcement [23][24][25][26][27]. In many cases, the saturated permeability values exceed the unsaturated permeability values [23][24][25][26][27][28]. Many possible reasons for this discrepancy have been reported; capillary effects, void entrapment, and fiber deformation problems, etc.…”
Section: Background and Theorymentioning
confidence: 99%
“…Results show significant variance ($20-30%) in permeability for the same test cases, caused primarily by the inherent textile/preform uncertainties and secondarily by different hardware/procedures of permeameters [76]. This result has triggered research that focuses on permeameter characteristics and their procedures: dipoles of permeameter characteristics have been investigated and compared [45,61,[77][78][79][80], such as saturated or unsaturated permeability determination, continuous (i.e. camera) or discrete (i.e.…”
Section: Materials Characteristics Used In Simulationsmentioning
confidence: 99%
“…They can also be used in a modified Darcy law in order to estimate saturated permeability from transient flow which can be a good complement to work from the literature [33,34].…”
Section: Determination Of Equivalent Capillary Pressurementioning
confidence: 99%
“…It appears that the measurement of components of the permeability tensor is very sensitive to the method used [29][30][31][32]. Moreover permeability has to be considered depending on the degree of saturation of porous medium [33,34]. The main issue is that on unsaturated flows, capillary effects occur during filling of the multi-scales cavities formed by tows and fibres [7,1].…”
Section: Introductionmentioning
confidence: 99%